The biodiversity and ecosystem service contributions and trade-offs of forest restoration approaches - Hua, Fangyuan; Bruijnzeel, L. Adrian; Meli, Paula; Martin, Philip A.; Zhang, Jun; Nakagawa, Shinichi; Miao, Xinran; Wang, Weiyi; McEvoy, Christopher; Peña-Arancibia, Jorge Luis; Brancalion, Pedro H. S.; Smith, Pete; et al. (Science (American Association for the Advancement of Science), 2022)
Forest restoration is being scaled up globally to deliver critical ecosystem services and biodiversity benefits; however, there is a lack of rigorous comparison of cobenefit delivery across different restoration approaches. Through global synthesis, we used 25,950 matched data pairs from 264 studies in 53 countries to assess how delivery of climate, soil, water, and wood production services, in addition to biodiversity, compares across a range of tree plantations and native forests. Benefits of aboveground carbon storage, water provisioning, and especially soil erosion control and biodiversity are better delivered by native forests, with compositionally simpler, younger plantations in drier regions performing particularly poorly. However, plantations exhibit an advantage in wood production. These results underscore important trade-offs among environmental and production goals that policy-makers must navigate in meeting forest restoration commitments. Reforestation is promoted globally as one way to mitigate climate change through the storage of carbon in woody growth and ecosystem services such as control of soil erosion and management of water supplies. Hua et al . assessed the relative performance of plantation and native forest in achieving these goals (see the Perspective by Gurevitch). Synthesizing data from the world’s major forest biomes, they found that native forests consistently delivered better performance than plantations in the provision of the three major ecosystem services, with additional benefits for biodiversity. The discrepancy was particularly marked in in warmer and drier regions. These findings show that the benefits of reforestation will be best achieved through the restoration of native forests rather than extensive plantation programs. —AMS Critical ecosystem services and biodiversity are typically delivered more effectively by native forests than by plantations.